The Phenomenon of Early Marriage in Tanjung Agung District, Muara Enim Regency (Islamic Legal Analysis and Solutions) - Wahyudin Ibrahim; Budi Kisworo; Rifanto Bin Ridwan (QONUN: Jurnal Hukum Islam dan Perundang-undangan, 2025)
Early marriage in Tanjung Agung District, Muara Enim Regency, is a crucial social issue characterized by a dualism of norms between positive law in Law No. 16 of 2019 and permissive socio-religious norms. This study aims to analyze the phenomenon of early marriage in depth, identify its causal factors, and examine the role of the Religious Affairs Office (KUA) in addressing it from the perspective of Islamic Family Law. Using qualitative methods with a descriptive juridical approach, data were collected through in-depth interviews with various key informants including KUA officers, religious leaders, community leaders, parents, and young couples and was further supported by observation and documentation studies.The results indicate that state law is ineffective in the face of dominant social norms. This practice is driven by a complex combination of economic factors, education, and moral justifications to prevent promiscuity, yet consistently produces greater negative impacts (harm). It was also found that the community's understanding of marriage readiness remains narrow, focusing on physical aspects while neglecting mental and economic maturity. As a result, marriage dispensations have shifted from being a child protection instrument to a reactive solution to social problems. The Religious Affairs Office (KUA) has played a vital role as an educational agent, but its effectiveness is hampered by strong traditions and significant gaps in ongoing post-marital support. This research confirms that effective interventions require a holistic approach that addresses economic aspects, reconstructs religious understanding, and strengthens post-marital support systems